The PlA1/A2 polymorphism of glycoprotein IIIa as a risk factor for stroke: a systematic review and meta-analysis. - Christopher N Floyd; Benjamin H Ellis; Albert Ferro (PLoS ONE)
Background The PlA1/A2 polymorphism of glycoprotein IIIa (GPIIIa) has been reported to be associated with risk of stroke in some studies, although other studies suggest no such association. This meta-analysis and systematic review was conducted to investigate the hypothesis that carriage of the PlA2 allele is a risk factor for stroke. Methods Electronic databases (MEDLINE and EMBASE) were searched for all articles evaluating carriage of the PlA2 allele and the incidence of stroke. Pooled odds ratios (ORs) were calculated using fixed-effect and random-effect models. Findings A total of 35 articles were eligible for inclusion, of which 25 studies were suitable for statistical analysis. For carriage of the PlA2 allele, OR 1.12 (n = 11,873; 95% CI = 1.03-1.22; p = 0.011) was observed for the incidence of stroke in adults, with subgroup analyses identifying the association driven by stroke of an ischaemic (n = 10,494; OR = 1.15, 95% CI = 1.05-1.27; p = 0.003) but not haemorrhagic aetiology (n = 2,470; OR = 0.90, 95% CI = 0.71-1.14; p = 0.398). This association with ischaemic stroke was strongest in individuals homozygous for the PlA2 allele compared to those homozygous for wild-type PlA1 (n = 5,906; OR = 1.74, 95% CI = 1.34-2.26; p<0.001). Subgroup analysis of ischaemic stroke subtypes revealed an increased association with stroke of cardioembolic (n = 1,271; OR 1.56, 95% CI 1.14-2.12; p = 0.005) and large vessel (n = 1,394; OR = 1.76, 95% CI 1.34-2.31; p<0.001) aetiology, but not those of small vessel origin (n = 1,356; OR = 0.99, 95% CI 0.74-1.33; p = 0.950). Egger's regression test suggested a low probability of publication bias for all analyses (p>0.05). Conclusions The totality of published data supports the hypothesis that carriage of the PlA2 polymorphism of GPIIIa is a risk factor for ischaemic strokes, and specifically those of cardioembolic and large vessel origin.